(untitled) (Italian Journal of Public Health, 2012)
Background: patients with congenital heart defects, developing right ventricular outflow tract (rVoT) dysfunction, can face repeated open chest interventions over their lifetime. repeating surgery increases difficulties and procedural risks, and exposes patients to burdensome and long recovery times that may induce them to postpone the treatment, with possible severe and irreversible consequences for their health. The percutaneous procedure was introduced to delay the need for open chest surgery. uncertainties still exist regarding the lifelong consequences that may result from adopting different treatment strategies. current decisions on treatment depend on patients’ clinical needs, but also on physicians’ experience and opinion, patients’ preferences, and procedural costs. The objective is to identify which treatment characteristics influence decisions on how to treat patients with rVoT dysfunction. Methods: a literature review was conducted, followed by a discussion with a panel of experts. Ten treatment characteristics, potentially relevant for treatment, were identified and rated in a survey, according to the importance assigned to each characteristic by specialist physicians, patients and/or their caregivers. Results: while some characteristics appear to be more important (risk of severe complications associated with intervention delays) or less important (scar) to both physicians and patients/caregivers, other characteristics are rated differently in importance depending on subjects consulted, e.g., risk of complications during the months post intervention was among the most important characteristics for patients/caregivers, but the fifth most important characteristic for physicians. Conclusions: to optimize benefits and efficiency of the treatment strategies, perceptions and opinions from the different subjects involved, together with patients’ clinical needs and overall costs, should be considered in decision-making....